Structural, magnetic, electrical and magnetotransport properties of (La,Pr)₁₋ₓ(Sr,Ba)ₓMnO₃ bulk, single and bi-layer thin films - Ming, Albert Gan Han (2014)
Colossal magnetoresistance (CMR) compound which exhibit large magnetoresistance value associated with its ferromagnetic-paramagnetic phase transition gain interest from researchers since 1950s. Large drop in resistivity in CMR material at very low magnetic field (0-0.1T) at low temperature (80K) gained further attentions from researchers. This low field magnetoresistance effect can be altered by grain size distribution. Fabrication and characterization of CMR thin film have been done in recent years to study the possibility in various application. Magnetic properties of thin film can be altered by introducing a pinning layer for bilayer film. Very limited report of coupling and stacking sequence of two CMR layer can be found. In this work, several investigation have been done. Effect of various average cation size of rare earth element and alkaline earth element at A-site towards physical properties in (La,Pr)0.67(Sr,Ba)0.33MnO3 system have been studied. La0.67Sr0.33MnO3(LSMO), Pr0.67Sr0.33MnO3(PSMO), La0.67Ba0.33MnO3(LBMO), and Pr0.67Ba0.33MnO3(PBMO) were synthesized by conventional solid state reaction route. Sub-micron grains were obtained for the bulk samples. Transformation from hexagonal to orthorhombic crystal structure was observed when La3+ was replaced by Pr3+. However, replacement of Sr2+ by Ba2+ in the compound only caused different microstructure formation. The difference in electrical, structural and magnetic properties in comparison to bulk samples are due to the difference in average cation size in A-site. Tp observed are >300 K for LSMO, 286 K for PSMO, 256 K for LBMO while PBMO shows Tp at 182 K and 150 K. Two Tp values in PBMO are due to the existing of core shell effect contributed by large difference in ionic size between rare earth and alkaline earth element. Tc observed for PSMO and PBMO are at 301 K and 184 K respectively. However, Tc of LSMO and LBMO were higher than 320 K similar as reported by other researchers. LSMO and PSMO were deposited on corning glass, MgO (100) and fused silica substrate by pulsed laser deposition technique (PLD). Grains obtained are in nano size and agglomerate in "island" like formation. Nano size cracks was observed due to difference in coefficient of thermal expansion between sample and substrate. Crystal structure retain upon converted into thin film of thickness ~2 μm. Lattice strain induced from the lattice mismatch between sample and substrate affected Mn-O-Mn octahedral bond angle and bond distance, affected metal-insulator transition temperature in each system. Weak ferromagnetic behavior below Tc observed in PSMO-F can be due to the extremely high value of lattice strain induced. Bilayer thin film was synthesize by coupling LSMO and PSMO in different stacking sequences on top of corning glass, MgO (100) and fused silica. Larger grain size in bilayer film is due to the greater diffusion at second deposition. Lattice strain observed in bilayer system is dependent on the stacking sequence of crystal structure of individual film. The observed Tp of the top layer does not change much but curie temperature of top layer seemingly mimic to buffer layer due to magnetic pinning effect. Enhancement of magnetoresistance in bilayer film might due to the increase of disorder in bilayer system. Pr0.67Sr0.33MnO3 with La0.67Sr0.33MnO3 as buffer layer, deposited on MgO (100) showed highest LFMR value which is -14.4% at 80 K and 0.1 T whereas the LFMR value at room temperature (300K) is -0.9%. CMR material can be used for low/high field magnetic field sensing device, land mine detector (Roul et al., 2001), as well as automotive sensors (NXP Semiconductors, 2006).